Cherchez la femme: Two Germanic suffixes, one etymology - Gąsiorowski, Piotr (De Gruyter, 2017)
The origin of the Germanic suffixes forming occupational titles and agent nouns – masculine *-ārijaz (the ancestor of Modern English -er) and its feminine counterpart reflected in Old English as -estre and in Modern as -ster – is an old problem in Germanic historical morphology. The masculine “agentive” suffix, which occurs in all the subgroups of Germanic, is generally presumed to be of Latin origin, though it occurs mostly with native derivational bases even in the earliest attested Germanic languages; the latter is believed to be native, but has no accepted etymology, and its limited range of occurrence in Germanic remains unexplained. It will be argued that the two suffixes are etymologically connected in a hitherto unsuspected way, that the traditional opinion about the origin of *-ārijaz should be revised, and that both suffixes have interesting Indo-European cognates outside Germanic.
Keywords: Proto-Germanic; morphology; Indo-European; Verner's law